Dissolving boundaries: Story-telling as self-representation. - Barrett, Estelle (Critical Arts: A South-North Journal of Cultural & Media Studies, 1996)
Examines story-telling as a process of negotiating boundaries by focusing on Filipino writer and epic chanter Marian Pastor Roces' narration of the 1980s revolution in the Philippines. Telling and retelling of stories as an opportunity for self-representation; Narration's resemblance of various practices of everyday life; Deployment of tactics in appropriation and reappropriation of language.